2009
DOI: 10.1111/j.1365-2125.2008.03306.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of short vs. long duration of antibiotic therapy for acute bacterial sinusitis: a meta‐analysis of randomized trials

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Treatment guidelines generally support that a 10–14‐day antibiotic regimen should be administered to uncomplicated acute bacterial sinusitis patients. • However, the level of evidence for such a recommendation is rather weak. • Treatment of such duration may have disadvantages compared with a shorter duration but equally effective regimen, including the promotion of bacterial drug resistance, poorest patient compliance, higher toxicity, and a greater overall economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 50 publications
(106 reference statements)
2
28
0
2
Order By: Relevance
“…A meta-analysis of 12 randomized controlled trials found no statistically significant difference between long-term and short-course antibiotics for cure or improvement of symptoms. 15 Five to 7 days of treatment with the appropriate antibiotic is considered effective for patients with uncomplicated ABS.…”
Section: Streptococcus Pneumoniae Haemophilus Influenzae Moraxella Camentioning
confidence: 99%
“…A meta-analysis of 12 randomized controlled trials found no statistically significant difference between long-term and short-course antibiotics for cure or improvement of symptoms. 15 Five to 7 days of treatment with the appropriate antibiotic is considered effective for patients with uncomplicated ABS.…”
Section: Streptococcus Pneumoniae Haemophilus Influenzae Moraxella Camentioning
confidence: 99%
“…Rather, we evaluated antimicrobial therapy of shorter duration than commonly used,30 in comparison with therapy of longer duration. It should be mentioned that findings similar to those presented herein referring to acute meningitis have also been demonstrated for other types of infectious diseases, such as acute bacterial sinusitis and community-acquired pneumonia, using the same methodology 31 32. Last but not least, findings of studies performed in developed countries may not directly relate to the actual clinical setting in developing countries, in which the issue of a shortened duration of therapy for bacterial meningitis is crucial.…”
Section: Discussionmentioning
confidence: 53%
“…В большинстве проведенных клинических исследованиях антибиотики назначаются на срок от 7 до 10 дней. Систематический обзор, включивший 12 исследований, не выявил разницы в клинической эффективности терапии и частоте разви-тия побочных эффектов у пациентов, получавших анти-биотики 3-7 дней, при сравнении с пациентами, полу-чавшими их 6-10 дней [22]. Таким образом, отсутствуют строгие рекомендации о длительности курса антибакте-риальной терапии, за исключением ее минимальной про-должительности в 5 дней с продолжением по усмотре-нию лечащего врача до 7-10 дней.…”
Section: таблицаunclassified